Anioł Pański zwiastował Józefowi. Teologia wcielenia w Mt 1,18b–25 - Linke, Waldemar (Colloquia Litteraria, 2022)
The papier is a study of Matthew 1,18b–25 focalized on the narrative form of expression of belief in Incarnation. The studied pericope is presented as a key element of the Matthew’s Infancy Gospel (Matthew 1–2). Analysis of the plot of narrative is completed with the study of the quotation of Is 7,9 used in Matthew 1,23 in the Greek version (LXX). Both, the narrative and the form of the quoted text chosen by the author of the gospel are focalized on the virginal conception of Jesus as a decisive argument for the divine origin of Jesus. Inner textual recipient of the message of Incarnation is St. Joseph, a model of believer.